KENYAMANAN TERMAL RUMAH TEPI SUNGAI, STUDI KASUS RUMAH TEPI SUNGAI KAHAYAN, PALANGKA RAYA, INDONESIA - Toding, Juprianto Bua’; Kindangen, Prof. J.I.; Sangkertadi, Prof. (Universitas Bina Taruna Gorontalo, 2015)
ABSTRAK Early settlement in the town of Palangka Raya began when the Dayak tribes started to build their traditional houses. The traditional houses were constructed in the river bank or even on the river water. These houses consisted of two types: the stilt houses and the floating houses. Since the area in which the houses are built is in the warm and humid climate, with the daily average air temperature above 28oC and the relative humidity above 85%, there is a curiosity whether inhabitants live in these houses were comfortable. A recent thermal comfort study has been conducted in these houses to see whether people were thermally comfortable This paper discusses this study and draws some conclusion from it. Keywords: thermal comfort, PMV, PPD, houses, riverside, Palangka Raya